Cervical duplex ultrasound for the diagnosis of giant cell arteritis with vertebral artery involvement. Issue 4 (5th April 2021) - Kargiotis, Odysseas; Psychogios, Klearchos; Safouris, Apostolos; Bakola, Eleni; Andreadou, Elizabeth; Karapanayiotides, Theodore; Finitsis, Stephanos; Palaiodimou, Lina; Giannopoulos, Sotirios; Magoufis, Georgios; Tsivgoulis, Georgios
ABSTRACT: Giant cell arteritis (GCA) is a systemic inflammatory arteriopathy of medium and large‐sized arteries, predominantly affecting branches of the external carotid artery. Ischemic stroke has been reported in 2.8–7% of patients diagnosed with GCA. The majority of ischemic strokes may involve the posterior circulation as a result of vertebral and/or, less frequently, of basilar artery vasculitis. Prompt diagnosis is crucial since high‐dose corticosteroid treatment is highly effective in preventing the occurrence or recurrence of ischemic complications, including posterior circulation ischemic stroke in cases with vertebrobasilar involvement. Cervical duplex sonography (CDS) of the temporal arteries is a powerful diagnostic tool with high sensitivity and specificity for the diagnosis of GCA. In cases with clinical suspicion or a temporal artery ultrasonographic confirmation of GCA, a detailed evaluation of the cervical, axillary, and intracranial arteries with CDS and transcranial‐duplex‐sonography, respectively, should be part of the ultrasound examination protocol. Specifically, signs of extracranial vertebral artery wall inflammation ("halo" sign) and focal luminar stenoses may be accurately depicted by ultrasounds in high‐risk patients or individuals with ischemic stroke attributed to GCA. In this review, we present three cases of GCA and posterior circulation ischemic complications that were initially evaluated with comprehensive neurosonology protocol and were promptly diagnosed with GCA based on the characteristic "halo" sign in the temporal and vertebral arteries. In addition, we discuss the relevant literature concerning the utility of CDS for the early diagnosis of GCA, focusing on the subtype with extracranial arterial involvement, particularly that of the vertebral arteries.